2018
DOI: 10.21608/ajas.2018.8210
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Accumulation in the Edible Parts of some Sewage Wastewater Irrigated Vegetable Crops

Abstract: Nowadays, using sewage wastewater in the irrigated agriculture causes hazardous environment impacts. Assessment of these negative effects is vital issue to prevent heavy metals to be introduced in the food chain. Field and laboratory studies were conducted at Ellwan, Mangabad and El-Madabegh villages, Assiut Governorate, in order to evaluate heavy metals concentrations in the edible parts of carrot, turnip and onion plantswhich were irrigated with sewage water (SW). The obtained results indicated that, the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…While Cd, Co, and Cr were below acceptable levels, and available B and Ni were at moderate amounts, the available Fe, Mn, Zn, and Cu Pb in soils exceeded legal limits. However, Roshdy [ 72 ] proved that heavy metal contamination existed in the soil of the communities of Ellwan, Mangabad and El-Madabegh villages in Assiut Governorate. The results obtained revealed that the concentrations of Pb, Cd, and Ni in the edible plants were greater than the permissible limit levels, while those of Zn and Cu were within the safe limit values.…”
Section: Resultsmentioning
confidence: 99%
“…While Cd, Co, and Cr were below acceptable levels, and available B and Ni were at moderate amounts, the available Fe, Mn, Zn, and Cu Pb in soils exceeded legal limits. However, Roshdy [ 72 ] proved that heavy metal contamination existed in the soil of the communities of Ellwan, Mangabad and El-Madabegh villages in Assiut Governorate. The results obtained revealed that the concentrations of Pb, Cd, and Ni in the edible plants were greater than the permissible limit levels, while those of Zn and Cu were within the safe limit values.…”
Section: Resultsmentioning
confidence: 99%